On Friction Reduction by Surface Modifications in the TEHL Cam/Tappet‐Contact‐Experimental and Numerical Studies - Marian, Max; Weikert, Tim; Tremmel, Stephan (Coatings, 2019)
The overall energy efficiency of machine elements and engine components could be improved by using new technologies such as surface modifications. In the literature, surface engineering approaches like microtexturing and the application of diamond-like carbon (DLC) coatings were frequently studied separately, with focus on a specific model contact and lubrication conditions. The contribution of the current study is to elucidate and compare the underlying friction reduction mechanisms of the aforementioned surface modifications in an applicationorientated manner. The study applied the operating conditions of the thermoelastohydrodynamically lubricated (TEHL) cam/tappetcontact of the valve train. Therefore, tribological cam/bucket tappet component Stribeck tests were used to determine the friction behavior of ultrashort pulse laser fabricated microtextures and PVD/PECVD deposited silicondoped amorphous carbon coatings. Moreover, advanced surface characterization methods, as well as numerical TEHL tribosimulations, were utilized to explore the mechanisms responsible for the observed tribological effects. The results showed that the DLCcoating could reduce the solid and fluid friction force in a wide range of lubrication regimes. Conversely, microtexturing may reduce solid friction while increasing the fraction of fluid friction.<br
Keywords: thermoelastohydrodynamic lubrication; DLCcoating; microtexturing; surface modification; friction mechanisms; energy efficiency; internal combustion engine; cam/tappetcontact